(3GdeQGLYI GdJTZjdjI h GdQbGHI GdOGNdjI (B/s - (3GdUMf, YHO GdaJGM eMeOs; (3GdSjO, SQGjG eMeO s ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2008)
(3GdQbGHI GdOGNdjI GdMOjKI GdeaGgje hGdCgOGa hGdJWhQ GdJGQjNj , GdQbGHI ef NdGd Jbjje GdCOGA eTcd GdQbGHI GdOGNdjI Ydi Cef hSdGeI GdeYdheGJ aj Xd HjFI JcfhdhLjG GdeYdheGJ ; GdGJLGgGJ GdMOjKI aj GdeQGLYI GdOGNdjI(B: (3GdeaGgje GdeYGjjQ , GdGjRh eQGLYI fXe GdGOGQI GdHjFjI GdLhOI GdTGedI GdYdGbI eY GdeQGLY GdNGQLj ; GWGQ GdeQGLYI GdOGNdjI GdJTZjdjI ,GdeQGLYI GdJTZdjI dYedjGJ OhQI GdGjQGOGJ hGdeJMUdGJ , GdeQGLYI GdJTZdjI dYedjGJ OhQI GdfabGJ hGdeOahYGJ ,GdeQGLYI GdJTZdjI dYedjGJ OOhQI GdeNRhf , GdeQGLYI GdJTZdjI dYedjGJ OhQIGdCLhQ hGdNOeGJ GdCaQGO ,GdeQGLYI GdJTZdjI dYedjGJ OhQIGdJehjds
Keywords: (3GdEOGQI GdeGdjIs; (3GdQbGHI GdeGdjIs; (3eQGLYI GdMSGHGJs